2016
DOI: 10.20472/te.2016.4.2.001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Feedback Practices in Formative Assessment in Rwandan Higher Education: A Multifaceted Approach Is Needed

Abstract: Inspired by the current scholarship that indicates that, if used well, formative assessment and feedback can advance student's learning, this paper explores the practices of feedback in formative assessment in Rwandan higher education, specifically at the University of Rwanda. The study used a qualitative approach with the aim of gaining lecturers' and students' perspectives on formative assessment and feedback; and exploring different ways formative assessment and feedback were practiced. Using data collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The study is the first of its nature that investigates the cognitive level of the questions in primary six English exams in Rwanda. Most literature on assessment in Rwandan education has mainly focused on higher education (Bahati et al, 2016 ; Mugisha, 2010 ; Tabaro, 2017 ). A handful of studies have investigated assessment in secondary schools only (Ndihokubwayo et al, 2020 ; Ngendahayo & Askell-Williams, 2016 ; Sibomana, 2016 ).…”
Section: Needs and Significance Of The Studymentioning
confidence: 99%
“…The study is the first of its nature that investigates the cognitive level of the questions in primary six English exams in Rwanda. Most literature on assessment in Rwandan education has mainly focused on higher education (Bahati et al, 2016 ; Mugisha, 2010 ; Tabaro, 2017 ). A handful of studies have investigated assessment in secondary schools only (Ndihokubwayo et al, 2020 ; Ngendahayo & Askell-Williams, 2016 ; Sibomana, 2016 ).…”
Section: Needs and Significance Of The Studymentioning
confidence: 99%
“…In Rwanda, as in many other countries, mathematics serves as a gateway subject that influences future academic and career opportunities (Bahati et al, 2016). Assessment is an integral part of the education process, playing a crucial role in shaping learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Timely feedback is crucial for effective learning. Bahati et al (2016) emphasized that feedback should be specific, actionable, and provided promptly to be most effective. In the context of mathematics education, studies indicated that feedback improves performance, particularly in helping students identify errors and understand the underlying concepts (Carless & Boud, 2018;Dayal, 2021;Evans, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations